Inventory Control of Medicine with Minimum-Maximum Stock Level at Ibu Fatmawati Soekarno Hospital Surakarta in 2023 - Anwar, Alifia Auriel; Cahyo, Lukito Mindi; Wijayanti, Tri (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: Inventory control prevents overstock and stockouts by monitoring availability, usage, while managing loss, damage, and expiration. Many hospitals struggle to manage inventory efficiently. Therefore, it is crucial to categorize drug supplies based on usage and investment values to balance supply and demand.Objectives: The study aims to categorize drug supplies based on their usage and investment values and then calculate the minimum and maximum stocks.Methods: This is a descriptive non-experimental study using cross-sectional data collected descriptively and retrospectively. Secondary data was used from drug information on SIM in 2023 and primary data from interviews. The results will be categorized using ABC categories, and inventory will be managed using the MMSL method. Additionally, the study will calculate the minimum and maximum stock as part of the investment process.Results: The ABC analysis of usage shows the percentage of drug items in groups A consists of 8.17% of items accounting for 70.06% of total usage, group B with 12.03% accounting for 20.41%, and group C with 79.80% accounting for 9.53%. Similarly, for investment value, group A accounts for 70.35%, group B for 20.16%, and group C for 9.50%. The MMSL method resulted in optimal safe, minimum, and maximum stock levels for each drug item.Conclusion: Grouping drugs into A, B, and C categories based on usage value and investment value can help to prioritize a drug, and inventory control with the MMSL method has a positive impact where there is a decrease in the number of purchases and purchase costs after the MMSL method.